Multiple cutaneous squamous cell carcinoma of the forehead in a patient with skin of color treated by wide local excision with adjuvant radiotherapy: a case report - Pari, Vishnupriya; Roy, Biswanath; Gorai, Surajit; Bhattacharya, Saptarshi; Shahid, Tanweer; Srivastava, Ritu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Cutaneous squamous cell carcinoma is the second most common non-melanoma skin cancer, characterized by the proliferation of keratinocytes, with an increasing incidence worldwide. In cases of perineural invasion, surgical excision followed by adjuvant radiotherapy is the preferred treatment. An intraoperative frozen section is necessary to determine the cancer-cell-free margin. A 80-year-old male presented to the outpatient department of our hospital with two fungating growths over his right forehead (size 2.7×1.2 cm) and right temple region (size 4×1.2 cm) for 5 years. An incisional biopsy of the growths revealed well-differentiated squamous cell carcinoma. There was no evidence of lymphadenopathy. The patient was treated successfully by wide local excision of the growths with an intraoperative frozen section to determine negative margins. Local defects of the forehead and right temple were reconstructed with a scalp rotation flap and a split skin thickness graft, respectively. The final histopathological examination showed moderately differentiated squamous cell carcinoma with resection-free margins. Forehead growth showed perineural invasion. The patient underwent 30 fractions of image-guided adjuvant radiotherapy in view of perineural invasion and to avoid local recurrence. The patient recovered well without any recurrences or complications. Surgical excision and reconstruction followed by adjuvant radiotherapy is the most effective method for treating cutaneous squamous cell carcinomas with perineural or lymphovascular invasion. Intraoperative frozen section is necessary to reduce recurrence rates and metastasis. Ours is a rare case of multiple cutaneous squamous cell carcinomas involving the forehead region.